A comparison of surgical outcomes between single-site robotic, multiport robotic and conventional laparoscopic techniques in performing hysterectomy for Benign indications - Natasha Gupta; D O Miranda Blevins; Jenny Holcombe; Robert Scott Furr (Wolters Kluwer Medknow Publications, 2020)
Objectives: Minimally invasive gynecologic surgery (MIGS) is the standard of care in performing hysterectomy for benign conditions. However, the choice of laparoscopic modality is largely dependent on surgeon's discretion, experience, and equipment availability. The objective of this study is: To compare outcomes between different minimally invasive approaches available for benign hysterectomies and to evaluate patient factors that influence the use of one approach over another. With this study, we sought to provide some objective criteria while deciding the appropriate MIGS technique. Materials and Methods: This is a retrospective study comparing perioperative outcomes between three techniques of minimally invasive hysterectomy: laparoscopy (LSC), multiport daVinci (MP-Rob) and single-site daVinci (SS-Rob). Patients undergoing benign hysterectomy (daVinci or conventional LSC) from January 2015 to July 2016 were included. 129 patients were identified and divided into: LSC (n = 44), MP-Rob (n = 36) and SS-Rob (n = 49). Results: There were statistically significant differences in age (MP-Rob46 ≠ LSC39), body mass index (BMI) (MP-Rob33 ≠ LSC27 or SS-Rob26.8), uterus weight (MP-Rob144 ≠ LSC102 or SS-Rob105) and operative time (LSC192 ≠ SS-Rob162.3 or MP-Rob163). Chi-square analyses revealed history of endometriosis and clinical endometriosis was statistically less common while leiomyomas were more common indications of MP-Rob. There was no statistically significant difference noted between length of stay, estimated blood loss, intraoperative, and post-operative complications between different surgical types. Conclusion: Patients with higher age, BMI, uterus weight and abnormal uterine bleeding were noted to undergo MP-Rob surgery. Patients with history of endometriosis were more likely to undergo LSC or SS-Rob surgery. Operative time was significantly less for daVinci hysterectomies (SS-Rob and MP-Rob) as compared to conventional LSC.